Do Nursing Students Have High Social Intelligence? Findings from Selected Nursing College, South India - Anju Philip.T; Sunitha P.P; Lakshmi S Babu; Vrinda R (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Social intelligence is the capacity to know oneself and to know others. Social intelligence can be expressed as a measure of social awareness, social skills and social information process. Nursing is a career, which demands high level of social intelligence. The aim of the present study was to describe the social intelligence among nursing students in a selected nursing college, south India.Methods: Descriptive survey design was used to conduct the study among 323 Nursing students South India. After getting ethical clearance and informed consent from the subjects the data were collected during the month in March 2020 using the standardised tool “Tromso Social Intelligence Scale”. Cluster random sampling was used to conduct the study. Nursing students currently undergoing their course are included in the study and those who were suspended or dismissed from their course or absent during the time of data collection were excluded from the study.Results: Among 323 subjects’ majority 229 (70.9 %) were in <20 years of age. Most of the subjects 315 (97.5%) were females. The subjects are studying in the first, second, third and fourth year of the course. Two hundred and thirty (71.2 %) are belonged to rural community. The average social intelligence score is around 90 [Q1= 85, Q3= 95]. It is observed that variables such as age, year of study and occupation of father are significantly associated with Social intelligence score [p<0.05].Conclusions: From the present study, it is observed that nursing students are equipped with good levels of social intelligence.